Plasma BCAA concentrations during exercise of varied intensities in young healthy men—the impact of endurance training - Gawedzka, Anna; Grandys, Marcin; Duda, Krzysztof; Zapart-Bukowska, Justyna; Zoladz, Jerzy A.; Majerczak, Joanna (PeerJ, 2020)
Background Branched-chain amino acids (BCAA) i.e., leucine (Leu), isoleucine (Ile) and valine (Val) are important amino acids, which metabolism play a role in maintaining system energy homeostasis at rest and during exercise. As recently shown lowering of circulating BCAA level improves insulin sensitivity and cardiac metabolic health. However, little is known concerning the impact of a single bout of incremental exercise and physical training on the changes in blood BCAA. The present study aimed to determine the impact of a gradually increasing exercise intensity—up to maximal oxygen uptake (VO2max) on the changes of the plasma BCAA [∑BCAA]pl, before and after 5-weeks of moderate-intensity endurance training (ET). Methods Ten healthy young, untrained men performed an incremental cycling exercise test up to exhaustion to reach VO2max, before and after ET. Results We have found that exercise of low-to-moderate intensity (up to ∼50% of VO2max lasting about 12 min) had no significant effect on the [∑BCAA]pl, however the exercise of higher intensity (above 70% of VO2max lasting about 10 min) resulted in a pronounced decrease (p < 0.05) in [∑BCAA]pl. The lowering of plasma BCAA when performing exercise of higher intensity was preceded by a significant increase in plasma lactate concentration, showing that a significant attenuation of BCAA during incremental exercise coincides with exercise-induced acceleration of glycogen utilization. In addition, endurance training, which significantly increased power generating capabilities at VO2max (p = 0.004) had no significant impact on the changes of [∑BCAA]pl during this incremental exercise. Conclusion We have concluded that an exercise of moderate intensity of relatively short duration generally has no effect on the [∑BCAA]pl in young, healthy men, whereas significant decrease in [∑BCAA]pl occurs when performing exercise in heavy-intensity domain. The impact of exercise intensity on the plasma BCAA concentration seems to be especially important for patients with cardiometabolic risk undertaken cardiac rehabilitation or recreational activity.
Keywords: BCAA; Incremental exercise; Endurance training; Maximal oxygen uptake